Philanthropy as a Sustainability Strategy in an Inclusive Pesantren Serving Marginalized Groups at Al-Fatah Yogyakarta - Insani, Wahyu; Imam Machali; Khusni Nur Rohman (Sunan Kalijaga International Journal on Islamic Educational Research, 2025)
The persistence of child beggars in Lhokseumawe City indicates that child protection and social welfare measures mandated by Aceh Qanun Number 11 of 2013 have not been implemented optimally. This study analyzes the implementation of the Qanun in protecting and handling child beggars and identifies the obstacles affecting its implementation. A descriptive qualitative approach was employed in Lhokseumawe City. Data were collected through observation, interviews, and documentation involving nine informants from the Social Affairs Office, the Civil Service Police Unit and Wilayatul Hisbah, a social foundation, community members, and child beggars. Data were analyzed through reduction, presentation, and conclusion drawing using the policy implementation dimensions of communication, resources, disposition, and bureaucratic structure. The findings show that the policy has been implemented through inter-agency coordination, street enforcement, data collection, guidance, social and religious advice, and repatriation to families or areas of origin. However, implementation remains oriented toward temporary enforcement rather than continuous rehabilitation. Public socialization is limited, the shelter is no longer functioning, facilities and operational budgets are inadequate, and sustainable empowerment programs are unavailable. Child beggars also tend to return to begging because of economic pressure, habitual behavior, peer influence, easy income, and continuing donations from the public. Strengthening budgets, shelters, rehabilitation, family assistance, and sustained public education is therefore required.